Perancangan Instalasi Listrik Musolah Nurul Fadillah Kp. Cibendil Ds. Maja Kab. Lebak Banten - Sunardi; Muhamad Ikhsan Muzaky; Pramudya Bayu Andriyantoro; Amando Surbakti; Estu Ezza Pratama; Muhamad Rahman (CV. Multi Kreasi Media, 2025)
This community service activity aims to assist in the planning and design of a safe and efficient electrical installation for Musholah Nurul Fadillah, located in Cibendil Village, Maja District, Lebak Regency, Banten. The installation is designed based on the Indonesian National Standard (SNI), involving power requirement analysis, selection of electrical components, and technical calculations such as cable sizing and panel capacity. The design includes proper placement of lighting points, sockets, and switches tailored to the room’s function and worship activities. Safety aspects are addressed through the use of protective devices such as MCBs (Miniature Circuit Breakers) and ELCBs (Earth Leakage Circuit Breakers). With a total of 15 lighting points, 10 sockets, and 5 switches, this activity is expected to provide practical solutions and contribute positively to the improvement of worship facilities for the local community.